2010
DOI: 10.1190/1.3427538
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prior models for a blocky inversion of seismic AVA data

Abstract: Resolving thinner layers and focusing layer boundaries better in inverted seismic sections are important challenges in exploration and production seismology to better identify a potential drilling target. Many seismic inversion methods are based on a least-squares optimization approach that can intrinsically lead to unfocused transitions between adjacent layers. A Bayesian seismic amplitude variation with angle (AVA) inversion algorithm forms sharper boundaries between layers when enforcing sparseness in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…To take advantage of this feature, it could be useful to modify the smoothness constraints in the GaussNewton algorithm, such that an L 1 norm regularization would be applied. Several studies have demonstrated that L 1 norm regularization better reconstructs model edges (e.g., Theune, 2010). This could be implemented using the approach proposed by Farquharson and Oldenburg (1998).…”
Section: Discussionmentioning
confidence: 97%
“…To take advantage of this feature, it could be useful to modify the smoothness constraints in the GaussNewton algorithm, such that an L 1 norm regularization would be applied. Several studies have demonstrated that L 1 norm regularization better reconstructs model edges (e.g., Theune, 2010). This could be implemented using the approach proposed by Farquharson and Oldenburg (1998).…”
Section: Discussionmentioning
confidence: 97%
“…To constrain and stabilize the AVO inversion problem, however, some scholars have endeavored to adopt different prior probabilistic constraints following a Bayesian framework. Based on the classical work on geophysical probabilistic inverse theory (e.g., Tarantola, 1987;Menke, 1989), they employ the Bayesian statistical method to formulate the AVO inversion problem successfully (Gouveia, 1996;Sen and Stoffa, 1996;Gouveia and Scales, 1998;Buland and Omre, 2003;Riedel et al, 2003;Downton, 2005;Rabben et al, 2008;Karimi et al, 2010;Theune et al, 2010;Alemie and Sacchi, 2011;Zong et al, 2013). In the literature listed above, some are using the linearized approximations (see Aki and Richards, 1980;Shuey, 1985;Smith and Gidlow, 1987;Gray et al, 1999;Ursin and Dahl, 1992;Wang, 1999;Ursenbach, 2002) and some are employing the accurate Zeoppritz equations (Simmons and Backus, 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Since the occurrence of AVO analysis proposed by Ostrander (1984), it has received considerable attention in the field of seismic exploration (Aki and Richards, 1980;Smith and Gidlow, 1987;Swan, 1993;Simmons and Backus, 1996;Buland and Omre, 2003;Riedel et al, 2003;Downton, 2005;Rabben et al, 2008;Theune et al, 2010;Alemie and Sacchi, 2011;Zhang et al, 2013;Zong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the coefficients of such approximations can be related to physical parameters associated to lithology, fluid, and porosity, key issues for the characterisation of hydrocarbon reservoirs (Ostrander ; Castagna, Swan and Foster ; Smith and Gidlow ; Chopra and Castagna ). Beyond the AVA/AVO analysis, AVA/AVO data inversion provides a more direct means to obtain estimates of the physical parameters of interest, such as the P‐ and S‐wave velocities and density (Buland and Omre ; Theune, Jensås and Eidsvik ).…”
Section: Introductionmentioning
confidence: 99%